Is the Privacy of Network Data an Oxymoron? - Fienberg, Stephen E. (Journal of Privacy and Confidentiality, 2013)
While social networks are now a part of everyday life for the vast majority of people using computers, smartphones, and tablets, privacy is but an afterthought. Google+ has in excess of 100 million users a month while Facebook has topped 1 billion. Other more specialized networks such as Linked-in add to the fray. But from a privacy perspective the biggest concern for users should be the efforts to integrate the networking apps into all other forms of online activity as well as the constant effort to link additional data to network information, in addition to the network owners’ efforts to market that information to third party vendors. Further, Facebook and other networking sites have already begun to build search capabilities and other facilities into their systems that extend the information they collect from users even further. What protections do users really have?